Effectiveness of low-intensity pulsed ultrasound on osteoarthritis: molecular mechanism and tissue engineering - Zhou, Jing; Ning, Eryu; Lu, Lingfeng; Zhang, Huili; Yang, Xing; Hao, Yuefeng (Frontiers in Medicine, 2024)
Osteoarthritis (OA) is characterized distinguished by pathological changes alterations in the synovial membrane, articular cartilage, and subchondral bone. P, resulting in physical symptoms include discomfortsuch as pain, deformity, and motor impairmentimpaired mobility. An increasing number ofNumerous research studies have confirmedvalidated the efficacyeffectiveness of lowintensity pulsed ultrasound (LIPUS) in OA treatment. The pPeriodic mechanical sound waves from generated by LIPUS can alleviate mitigate cellular ischemia and hypoxia, induce vibration and collision, yield significant produce notable thermal and non-thermal effects, modify alter cellular metabolism, accelerate expedite tissue metabolism, enhance nutrition, and hasten the repair, improve nutrient delivery, and accelerate the healing process of damagedinjured tissues. Its The efficacyeffectiveness and precisespecific mechanism of LIPUS is currently under investigation. This review provides an overview of LIPUS's potentialare still being studied, though. However, its effectiveness and precise mechanism are still under investigation. This review summarizes LIPUS's role in OA the treatment of OA, from considering various perspectives such as the synovial membrane, cartilage, subchondral bone, and tissue engineering. to promote It aims to facilitate interdisciplinary scientific research and further exploration of LIPUS as a complementarysupplementary technique to existingother methods or surgery. while ongoing Ongoing research is focused onseeks to determininge the optimal LIPUS dosage, frequency, timing, and treatment strategy of LIPUS for OA. Further Additional researchinvestigation is necessary torequired to elucidate clarify the precisespecific mechanism of action and potential effects impacts on cellscellular, animals, and humans before implementing it systems prior to its integration into therapeutic applicationssettings.